2021
DOI: 10.3390/biom11081214
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Nicotinamide N-Methyltransferase as a Potential Biomarker to Predict the Oncological Outcomes for Urological Cancers: An Update

Abstract: Nicotinamide N-methyltransferase (NNMT) catalyzes the N-methylation reaction of nicotinamide, using S-adenosyl-L-methionine as the methyl donor. Enzyme overexpression has been described in many non-neoplastic diseases, as well as in a wide range of solid malignancies. This review aims to report and discuss evidence available in scientific literature, dealing with NNMT expression and the potential involvement in main urologic neoplasms, namely, renal, bladder and prostate cancers. Data illustrated in the cited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 113 publications
(141 reference statements)
0
21
0
Order By: Relevance
“…BUC is associated with abnormal DNA methylation, and disruption of the methylation pattern establishment mechanism may result in deregulation of DNA methyltransferases and demethylases and altered metabolism of methyl groups [ 37 ]. In BUCs, several methyltransferases are upregulated [ 38 , 39 , 40 ]; their enhanced activity may result in depletion of methyl donors, thus potentially inducing an hypomethylation of gene promoters.…”
Section: Discussionmentioning
confidence: 99%
“…BUC is associated with abnormal DNA methylation, and disruption of the methylation pattern establishment mechanism may result in deregulation of DNA methyltransferases and demethylases and altered metabolism of methyl groups [ 37 ]. In BUCs, several methyltransferases are upregulated [ 38 , 39 , 40 ]; their enhanced activity may result in depletion of methyl donors, thus potentially inducing an hypomethylation of gene promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Recently in cancer research, overexpression of enzymes has been found in various cancer types [ 134 ]. In BC, overexpression of nicotinamide N-methyltransferase (NNMT) in urine is a novel biomarker studied in association with progression and aggressiveness [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…It seems arbitrary to compare the results of this study with those of the current specialized literature when the cut-off values as well as the types of urine sampling methods investigated were different (voided urine, urothelial brushing, urothelial washing, and passively collected urine). Comparing the analyses for the above-mentioned biomarkers, no difference in sensitivity or specificity was found between the NMP22 test kit (cut-o >10 U/mL) and the BTA Stat in different stages and tumor grades [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a proposed test for urological neoplasms that detects Nicotinamide N-Methyltransferase (NNMT) in exfoliated cells extracted from urine samples obtained from Bca patients and healthy individuals. A significant difference was observed between urine samples from patients suffering from Bca and those from controls [ 18 ]. There is no doubt that further and detailed research is needed on this marker.…”
Section: Introductionmentioning
confidence: 99%